Exploring a Digital Banking Talent Management Framework at a Banking Institution in South Africa - Asanda Rose-Mary Nesindande; Musawenkosi Donia Saurombe; Renjini Mary Joseph (SAGE Open)
This research explored a South African bank that was undergoing the implementation of advanced digital technologies at the time of the study. The aim of the research was to develop a framework for talent management amid advanced digitalisation within the bank. This research used a qualitative case study approach, and 18 one-on-one interviews were conducted with employees from the bank, selected through purposive sampling. Thematic analysis was used on the qualitative data collected, by applying an initial inductive coding process to the interview transcripts, followed by two further coding processes that gave rise to precise themes and subthemes. We found that digital technologies influenced the talent management value chain within the bank. These technologies require the transformation of talent management processes and practices. We also found that a reimagined Human Capital function delivery is required from the Human Capital function and Human Capital professionals. We then established that the delivery must encompass a digitised Human Capital function and Human Capital must operate as a strategic business partner, which must become a change management agent by partnering with business leaders to lead digital transformations in the bank. Overall, the research revealed that a sound response to the Fourth Industrial Revolution requires a new approach to talent management within the selected bank, and such an approach must be continuously recalibrated as and when new and substantially impacting technologies arise. This paper, therefore, offers unprecedented insights into the key talent management elements to be implemented in the bank during the adoption of advanced digital technologies.